Redesign of Squared-Profile Wood Sanding Machine for Work-Position and Productivity Improvement (Case study on Abu Production Handycraft, Pleret, Bantul, Yogyakarta) - Kristanto Agung; Saputra Agung (Agroindustrial Journal, 2020)
Abu Production Handycraft was a small and medium enterprise (SME) that produced various types of handicraft products, such as tissue boxes, lamp cups, ashtrays, fruit baskets, flowerpots, flower vases, plaques, trays, souvenirs, and other types of wooden craft product. One of production processes was sanding process which was performed by the operator while in sitting position on a small bench for long time. It caused the worker worked with the back in bent position, head bowed, elbows and both legs include knees folded. Standardised Nordic Questionnaires (SNQ) revealed that the worker suffered from pain in the neck, shoulder, elbow, wrist, back, buttock, and knee. So, it could effect on the work productivity. The objective of this research was to redesign of squared-profile wood sanding machine for Work-position and Productivity Improvement. The concept of ergonomics was applied for work facilities designing. The discomfort perceived, standard time, and work productivity would be measured for comparing between pre and post redesigning conditions on this research. The anthropometric data was taken as reference for the dimension of sanding machine design which matched to the body dimension of the worker. SolidWorks software was used in this research for sanding machine designing. The result showed a decrease on the level of discomfort of 70% into 10%. Regarding to the standard time, the result showed 20.96 minutes/unit and 7.99 minutes/unit for initial and final condition, respectively. It indicated a decrease of 61.88% in term of standard time. Related to the standard output, it showed 3.00 units/minute for initial condition and 8.00 units/minute for final condition. It indicated that there was an increase of 166.67% in term of productivity when compared to the initial condition.